Objective demonstration and quantitation of musical learning in older adult novices across a 12-month online study - Anthony Chmiel; Roger T. Dean; Catherine J. Stevens; Jennifer MacRitchie (PLoS ONE, 2025)
This work aimed to objectively (mainly computationally) measure the extent to which 68 older adult novices developed specific musical abilities. The participants learned aural and keyboard performance skills in a 12-month online course with an expert piano teacher, spending six months each on a digital piano keyboard and an iPad virtual piano. Within each 6 months, 3 were devoted successively to each of melodic replication and improvisation. Teaching sought correctness of pitches/sequences (for replication), and introduction of systematic diversity thereof (for improvisation). We measured aural perception using melody detection and beat alignment tests; and replication and improvisation learning using computational measures of MIDI-recordings. Bayesian modelling showed that melody detection, replication and improvisation were learned successfully and seemingly progressively, while beat detection, and rhythmic precision in replication, which were not our focus, were not. These skills were retained over a 6-month follow-up period. Improvisation teaching was the bigger predictor of melody detection, and replication teaching of replication performance. Potential applications for these findings in learning contexts are discussed.